Utilization of Origin Bacteria-Pliek U (YNH11 Isolates) in Fermenting Process of Coconut Dregs Cocos (Nucifera L.) - H L Harahap; Yunilas; N Ginting; E Mirwandhono; A H Daulay (Jurnal Peternakan Integratif, 2018)
Coconut plants are common in Indonesia, which is the second largest copra producer in the world. Coconut dregs has never been used before, as result it is one of large wastes in Indonesia. The main problems of coconut dregs were the content of crude fiber and crude fat which are high and low crude protein. Special attention was needed to improve the nutritional content by using fermentation technology. Fermentation was used in this study by using bacteria which had derived from the coconut plant itself called pliek u, isolate (YNH11). This study was conducted for 3 months starting from April to July 2018 at the Animal Production Laboratory and the Laboratory of Animal Food Nutrition Sciences Faculty of Agriculture, University of North Sumatra. This research was designed using a Completely Randomized Design (CRD) factorial pattern of 3 x 3, with 3 replications where remarked as factor 1 was the various levels of bacterial inoculum YNH11 from pliek u and factor 2 was the duration of fermentation (incubation). the parameters measured were water content, dry ingredient , crude protein, crude fiber, crude fat, and ash content using proximate analysis. The results showed that coconut pulp fermentation using bacterial origin of pliek u (isolate YNH11) with the level of inoculum administration and fermentation time had an effect on the measured parameters. it eventually increased water content and crude protein, meanwhile it decresed crude fiber, crude fat, dry ingredient, and ash content as well.